Snapshot on Negative Electrode Materials for Potassium-Ion Batteries - Gabaudan, Vincent; Monconduit, Laure; Stievano, Lorenzo; Berthelot, Romain (Frontiers in Energy Research, 2019)
Potassium-based batteries have recently emerged as a promising alternative to lithium-ion batteries. The very low potential of the K+/K redox couple together with the high mobility of K+ in electrolytes resulting from its weak Lewis acidity should provide high energy density systems operating with fast kinetics. However, potassium metal cannot be implemented in commercial batteries due to its high reactivity. As safety is one of the major concerns when developing new types of batteries, it is therefore crucial to look for materials alternative to potassium metal that electrochemically insert K+ at low potential. Here, the different types of negative electrode materials highlighted in many recent reports will be presented in detail. As a cornerstone of viable potassium-ion batteries, the choice of the electrolyte will be addressed as it directly impacts the cycling performance. Lastly, guidelines to a rational design of sustainable and efficient negative electrode materials will be proposed as open perspectives.